WIPO IP Facts and Figures 2019 (WIPO Publication, 2019)
IP Facts and Figures serves as a quick reference guide covering four types of industrial property: patents, utility models, trademarks and industrial designs. It focuses primarily on application data, which is the most often used measure of IP activity. Trademark application data refer to class counts – the number of classes specified in applications. This affords a better comparison of international trademark filing activity across IP offices, as applications in some jurisdictions may specify multiple classes of goods and services, while others require a separate application for each class. Similarly, industrial design data refer to design counts, that is, the number of designs contained in applications. IP Facts and Figures sirve como una guía de referencia rápida que cubre cuatro tipos de propiedad industrial: patentes, modelos de utilidad, marcas registradas y diseños industriales. Se centra principalmente en los datos de la aplicación, que es la medida de actividad de IP más utilizada. Los datos de solicitud de marca se refieren a recuentos de clases: el número de clases especificado en las solicitudes. Esto permite una mejor comparación de la actividad de registro de marcas internacionales en las oficinas de PI, ya que las solicitudes en algunas jurisdicciones pueden especificar múltiples clases de productos y servicios, mientras que otras requieren una solicitud separada para cada clase. Del mismo modo, los datos sobre diseños industriales se refieren a recuentos de diseños, es decir, el número de diseños contenidos en las solicitudes.